Post-Quantum Cryptography and Legal Frameworks: Strengthening Uzbekistan’s Cybersecurity and Intellectual Property Protection - Abdikhakimov, Islombek (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
The rapid development of quantum technology has significant implications for legal systems, particularly in the areas of cybersecurity, intellectual property, and digital sovereignty. The computational power of quantum computing to decrypt conventional encryption systems poses serious challenges to national information security. Developed countries have adopted post-quantum cryptographic policies to protect their data, while Uzbekistan still faces regulatory gaps in transitioning to more secure encryption systems. Furthermore, the increasing number of patents in quantum technology may create innovation barriers due to the phenomenon of patent thickets, which limit access to strategic technologies. The lack of regulatory clarity regarding legal liability for quantum-based artificial intelligence also creates uncertainty within Uzbekistan’s legal system, particularly in terms of transparency and accountability. Without adaptive regulations, Uzbekistan risks strategic data leaks and dependence on foreign actors in quantum technology development. Therefore, policy reforms are necessary, including post-quantum cryptography-based cybersecurity regulations, harmonization of intellectual property laws with international standards, and the implementation of regulatory sandboxes to test policies before widespread adoption. This study emphasizes that without concrete steps in quantum technology regulation, Uzbekistan risks falling behind in the global competition. A more flexible and progressive legal approach is required to ensure digital sovereignty, data security, and protection of domestic innovation. With the right policies, Uzbekistan can leverage quantum technology to drive its digital economy without compromising its strategic national interests.